Triple Positive Solutions of Boundary Value Problems for High-Order Fractional Differential Equation at Resonance with Singularities (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we investigate the existence of triple positive solutions of boundary value problems for high-order fractional differential equationat resonance with singularities by using the fixed point index theory and theLeggett-Williams theorem. The spectral theory and some new height functionsare also employed to establish the existence of triple positive solutions. Thenonlinearity involved is arbitrary fractional derivative, and permits singularity.
Keywords: Triple positive solution; Fractional differential equation; Resonance; Singularity.